The Level of Parents' Associations' Participation to School Administration in High Schools - Mustafa Bayrakçı; Serdar Dizbay (Sakarya University Journal of Education)
This research was carried out to identify the level of parents' associations' participation to school administration in Kocaeli city, İzmit district. Parents' associations' participation to school administration is identified according to the school administrators' perceptions. Moreover, the differences in their perceptions are examined according to the variables of their duty, age, and years of service. The population of the study was comprised of 27 principals and 83 vice principals who are working in the public highschools in Kocaeli, İzmit district. The data for the study were collected by using “personal information form” and “parents' associations' participation to school administration scale” which was developed by the researchers. Descriptive statistics and t-test were used to analyze the data collected for the study. Results of the study indicated that parents' associations participate to school administration in only economic concerns. Any significant differences were not found in school administrators' perceptions on parents' associations' participation to school administration according to their duties in school, age and years of service.